Taxonomic study of the leafhopper genus Agnesiella Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae) from China, with descriptions of 13 new species - Wang, Junjie; Zhang, Yalin; Huang, Min (Zootaxa, 2022)
Thirteen new species of the leafhopper genus Agnesiella Dworakowska, Agnesiella (Agnesiella) protensa, A. (A.) recurve, A. (A.) polita, A. (Draberiella) gaura, A. (D.) longisagittata, A. (D.) eleganta, A. (D.) glabra, A. (D.) exigua, A. (D.) mitrata, A. (D.) apiculata, A. (D.) tridigitata, A. (D.) lata and A. (D.) stipitata spp. nov., are described and illustrated. A. (A.) marginata and A. (D.) irma are recorded from China for the first time. A checklist and key to the species (males) from China in Agnesiella are provided.